2005
DOI: 10.1103/physrevc.72.055502
|View full text |Cite
|
Sign up to set email alerts
|

Electron energy spectra, fluxes, and day-night asymmetries of8B solar neutrinos from measurements with NaCl dissolved in the heavy-water detector at the Sudbury Neutrino Observatory

Abstract: Results are reported from the complete salt phase of the Sudbury Neutrino Observatory experiment in which NaCl was dissolved in the D 2 O target. The addition of salt enhanced the signal from neutron capture, as compared to the pure D 2 O detector. By making a statistical separation of charged-current events from other types based on event-isotropy criteria, the effective electron recoil energy spectrum has been extracted. In units of 10 6 cm −2 s −1 , the total flux of active-flavor neutrinos from 8 B decay i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
189
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 501 publications
(197 citation statements)
references
References 63 publications
6
189
0
2
Order By: Relevance
“…Nonzero neutrino mass is now well established [43][44][45][46][47][48][49][50][51][52][53][54][55][56]; therefore, it is crucially important to study the properties of these nonzero-mass neutrinos. One interesting question is whether neutrinos are Majorana or Dirac neutrinos [57,58].…”
Section: Lepton-number-violating Decays With ∆L =mentioning
confidence: 99%
“…Nonzero neutrino mass is now well established [43][44][45][46][47][48][49][50][51][52][53][54][55][56]; therefore, it is crucially important to study the properties of these nonzero-mass neutrinos. One interesting question is whether neutrinos are Majorana or Dirac neutrinos [57,58].…”
Section: Lepton-number-violating Decays With ∆L =mentioning
confidence: 99%
“…The combined results showed that m ν 1 > m ν 2 , which resolved one of two mass hierarchy ambiguities [43].…”
Section: Reactor Neutrinosmentioning
confidence: 74%
“…8 B solar neutrinos, φ(ν e ), and φ(ν µ or ν τ ), deduced from the SNO's CC, elastic scattering (ES), and NC results of the salt phase, where salts had been introduced to enhance the NC measurement [40]. The Super-Kamiokande ES flux is from [41].…”
Section: Fig 18: Fluxes Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Under this assumption there would be no observable mixing between the sterile and active neutrinos. This conclusion arises from considering the results from the SNO experiment [32] which demonstrate that any coupling between active and sterile neutrinos must take place in the third and fourth mass eigenstates. This would therefore require observation of oscillations at very small mass splittings which would not be possible with the baseline available to the MINOS experiment.…”
Section: Model With M 4 = Mmentioning
confidence: 99%